The Effectiveness Of Using Al-Khalil 2 Program On Reading And Evaluating Classical Poetry By Repetition Among Students At King Fahd University Of Petroleum And Minerals/ فاعلية استخدام برنامج الخليل 2 على قراءة وتقييم الشعر الفصيح بالتكرار لدى طلاب جامعة الملك فهد للبترول والمعادن - Abd AlKreem Bin Saleh Al-Zahrani (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2026)
This study highlights the improvement of reading classical poetry by repetition among students of King Fahd University of Petroleum and Minerals in Dhahran through the Khalil 2 program, which was able to measure the reader’s improvement and reveal the percentage of improvement each time he repeated the experience. The semi-experimental structure was used, the new Khalil 2 program, and the computer tools were investigated. The study concluded that the Khalil 2 program was effective in the effectiveness of reading classical poetry among the study.